Paroxetine Attenuates Chondrocyte Pyroptosis and Inhibits Osteoclast Formation by Inhibiting NF-κB Pathway Activation to Delay Osteoarthritis Progression - Zheng X; Qiu J; Gao N; Jiang T; Li Z; Zhang W; Gong Y; Hong Z; Hong H (Dove Medical Press, 2023)
Xiaohang Zheng,1,2 Jianxin Qiu,1,2 Ning Gao,3 Ting Jiang,1,2 Ze Li,1,2 Weikang Zhang,1,2 Yuhang Gong,1,2 Zhenghua Hong,1,2 Huaxing Hong1,2 1Orthopedic Department, Taizhou Hospital Affiliated to Wenzhou Medical University, Linhai, People's Republic of China; 2Enze Medical Research Center, Taizhou Hospital Affiliated to Wenzhou Medical University, Linhai, People's Republic of China; 3Department of Cardiovascular Surgery, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, People's Republic of ChinaCorrespondence: Huaxing Hong; Zhenghua Hong, Taizhou Hospital Affiliated to Wenzhou Medical University, No. 150, Ximen Street, Taizhou City, Zhejiang Province, People's Republic of China, Fax +86 0576-8512-0120, Email tzyyhhx@126.com; 0001hzh@163.comBackground: Osteoarthritis (OA), a common chronic joint disease, is characterized by cartilage degeneration and subchondral bone reconstruction. NF-κB signaling pathway-activated inflammation and NLRP3-induced pyroptosis play essential roles in the development of OA. In this study, we examine whether paroxetine can inhibit pyroptosis and reduce osteoclast formation, thereby delaying the destruction of knee joints.Methods: We employed high-density cultures, along with quantitative polymerase chain reactions and Western blotting techniques, to investigate the effects of paroxetine on extracellular matrix synthesis and degradation. The expression levels of NF-κB and pyroptosis-related signaling pathway proteins were examined by Western blotting and immunofluorescence. Furthermore, the impact of paroxetine on RANKL-induced osteoclast formation was evaluated through TRAP staining and F-actin ring fluorescence detection. To investigate the role of paroxetine in vivo, we constructed a mouse model with destabilization of the medial meniscus (DMM) surgery. Safranin O-Fast Green staining, Hematoxylin-Eosin staining, and immunohistochemistry were conducted to observe the extent of knee joint cartilage deformation. In addition, TRAP staining was used to observe the formation of osteoclasts in the subchondral bone.Results: In the in vitro experiments with ATDC5, paroxetine treatment attenuated IL-1β-induced activation of the pyroptosis-related pathway and suppressed extracellular matrix catabolism by inhibiting the NF-kB signaling pathway. In addition, paroxetine treatment decreased the expression of RANKL-induced osteoclast marker genes and reduced osteoclast formation. In animal experiments conducted in vivo, mice treated with paroxetine exhibited thicker knee cartilage with a smoother surface compared to the DMM group. Additionally, the formation of osteoclasts in the subchondral bone was reduced in the paroxetine-treated mice. Further analysis revealed that paroxetine treatment played a role in preserving the balance of the extracellular matrix and delaying knee joint degeneration.Conclusion: Paroxetine can inhibit pyroptosis and reduce osteoclast formation via inhibiting the NF-κB signaling pathway, suggesting that it may have therapeutic effects in patients with OA.Keywords: paroxetine, pyroptosis, inflammation, osteoclasts, osteoarthritis